2013
DOI: 10.1134/s0021364013100032
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of total cross sections and ratios of real to imaginary parts of hadron amplitudes

Abstract: The impact of different assumptions about high energy behavior of the total cross section of proton-proton interactions on the ratio of the real to imaginary part of the forward elastic scattering amplitude is analyzed. It is shown how experimental data about this ratio at LHC energies can help in the proper choice of the asymptotic dependence of the total cross section.The total cross sections and the ratios of real to imaginary parts of forward scattering amplitudes are tightly connected by dispersion relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Another, even less model-dependent, relation between σ tot and ρ can be obtained from dispersion relations [7,49]. If only the crossing-even component of the amplitude is considered, it can be shown that ρ is proportional to the rate of growth of σ tot with energy.…”
Section: Discussion Of Physics Implicationsmentioning
confidence: 99%
“…Another, even less model-dependent, relation between σ tot and ρ can be obtained from dispersion relations [7,49]. If only the crossing-even component of the amplitude is considered, it can be shown that ρ is proportional to the rate of growth of σ tot with energy.…”
Section: Discussion Of Physics Implicationsmentioning
confidence: 99%
“…was traditionally quoted. An interesting aspect of ρ is its predictive power in extrapolating the total cross-section to higher centre-of-mass energies via dispersion relations [13].…”
Section: Introductionmentioning
confidence: 99%
“…The recent measurements of proton-proton total cross sections at the LHC by the TOTEM collaboration [1][2][3][4], at total center-of-mass energy √ s = 7 TeV and √ s = 8 TeV, have helped in reviving the study of the high-energy behaviour of hadronic total cross sections [5][6][7][8]. The main theoretical problem in this context is providing a convincing explanation of the rise with energy of total cross sections observed in experiments, and a definite prediction of its functional form, in the framework of QCD.…”
Section: Introductionmentioning
confidence: 99%